2020
DOI: 10.1002/tpg2.20060
|View full text |Cite
|
Sign up to set email alerts
|

Comparison and evolutionary analysis of Brassica nucleotide binding site leucine rich repeat (NLR) genes and importance for disease resistance breeding

Abstract: The Brassica genus contains many agriculturally significant oilseed and vegetable crops, however the crop yield is threatened by a range of fungal and bacterial pathogens. Nucleotide Binding Site Leucine Rich Repeat (NLR) genes play important roles in plant innate immunity. The evolution of NLR genes is influenced by genomic processes and pathogen selection. At the whole genome level, whole genome duplications (WGDs) generate abundant gene copies, most of which are lost during genome fractionation. At sub‐geno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 77 publications
(206 reference statements)
1
7
0
Order By: Relevance
“…None of the NAM line alleles appear to contain the functional Ht1 allele, but the comparatively high level of PAV at this unclustered locus once again points to high variability being indicative of functional NLR loci. These findings are in keeping with work in several other species, which has repeatedly pointed to the role of NLR clusters with high PAV in conferring disease resistance (Dolatabadian et al, 2020;Walkowiak et al, 2020;Zhang et al, 2021).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…None of the NAM line alleles appear to contain the functional Ht1 allele, but the comparatively high level of PAV at this unclustered locus once again points to high variability being indicative of functional NLR loci. These findings are in keeping with work in several other species, which has repeatedly pointed to the role of NLR clusters with high PAV in conferring disease resistance (Dolatabadian et al, 2020;Walkowiak et al, 2020;Zhang et al, 2021).…”
Section: Discussionsupporting
confidence: 90%
“…Cross-species comparisons within Brassica have shown that such complex NLR loci are subject to frequent birth and death events, with all members of some large NLR clusters showing high sequence homology to a singleton NLR of a closely related species (Fu et al, 2019;Zhang et al, 2021). More recently conducted pangenomic analyses have further shed light on the high level of intraspecies NLR diversity.…”
mentioning
confidence: 99%
“…Species-specific NLR gene duplications and clustering patterns have been reported earlier (Dolatabadian et al ., 2020; Inturrisi et al ., 2020; Zhang et al ., 2021; Zhang et al ., 2016). In our study also, we find that NLR clusters in the B-genome of diploids and tetraploids are collinear, however, there are changes in the NLR gene content within these clusters.…”
Section: Discussionmentioning
confidence: 99%
“…Several candidate CR genes have been identified to encode NLR proteins in B. rapa (Hatakeyama et al, 2017(Hatakeyama et al, , 2022Huang et al, 2017;Matsumoto et al, 2012;Wang et al, 2022;Yang et al, 2022;Zhang et al, 2021). CRa and Crr1a were successfully iso- and CRA8.1b, and those three genes could be responsible for the clubroot resistance, the TIR-NBS-LRRs BraA08g039211E…”
Section: Club Root Re S Is Tan Cementioning
confidence: 99%
“…Due to the lack of CR genes in B. napus (canola, genome AACC) germplasm, the canola progenitor B. rapa (Chinese cabbage, genome AA) is considered as a major source in CR breeding (Huang et al, 2017 ; Yang et al, 2022 ). Several candidate CR genes have been identified to encode NLR proteins in B. rapa (Hatakeyama et al, 2017 , 2022 ; Huang et al, 2017 ; Matsumoto et al, 2012 ; Ueno et al, 2012 ; Wang et al, 2022 ; Yang et al, 2022 ; Zhang et al, 2021 ). CRa and Crr1a were successfully isolated and characterized from Chinese cabbage lines of B. rapa , and both confer resistance to clubroot and encode TNLs (Hatakeyama et al, 2013 ; Ueno et al, 2012 ).…”
Section: Clubroot Resistancementioning
confidence: 99%